Experimental study on thermo-physical and rheological properties of stable and green reduced graphene oxide nanofluids: Hydrothermal assisted technique. Issue 9 (2nd September 2017) - Sadri, Rad; Zangeneh Kamali, K.; Hosseini, M.; Zubir, Nashrul; Kazi, S. N.; Ahmadi, Goodarz; Dahari, Mahidzal; Huang, N. M.; Golsheikh, A. M.
ABSTRACT: In this study a dehydration hydrothermal technique has been used to introduce a simple, environmentally friendly and facile method for manufacturing highly dispersed reduced graphene oxide for improving the thermo-physical and rheological properties of heat transfer liquids. The hydrothermal reduction of graphene oxide was verified by various characterizations methods such as UV–visible absorption spectroscopy, Zeta potential, Raman spectroscopy, X-ray photoemission spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and transmission electron microscopy. A thorough investigation was conducted on the thermo-physical properties of reduced graphene oxide at concentrations of 0.02, 0.04, 0.06, and 0.08 wt% under different temperatures. Significant improvements in electrical and thermal conductivity were obtained by adding a small amount of hydrothermal-assisted reduced graphene oxide (h-rGO) in the suspension. The viscosity and density remained relatively unchanged with the increase of concentrations where the pH was maintained within the desirable value, despite the fact that no additive was used during the reduction process. It is noteworthy to highlight that the h-rGO aqueous suspensions have shown Newtonian behavior. Results indicated that the h-rGO could be employed as a promising additive for conventional heat transfer liquids for different thermal applications. GRAPHICAL ABSTRACT: